Pemberdayaan Masyarakat Perumahan Desa Ajibarang Wetan Banyumas Jawa Tengah dalam Toleransi Antar Umat Beragama - Nur Kholipah, Sinta; Sarpini, Sarpini; Mufaizin, Mufaizin (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Indonesia is a country rich in diversity. Indonesia's diversity includes differences in ethnicity, culture, customs, language, and religion. To maintain this diversity, there must be an attitude of tolerance, mutual respect and respect for one another. This tolerance of diverse people can be realized in Indonesia, one of which is the Green Shapire Rasidance Housing in Ajibarang Village, Ajibarang District, Banyumas Regency. Green Shapire Rasidance housing in Ajibarang Wetan Village is a modern housing estate where the community embraces three religions, namely: Islam as the majority religion, and two other religions, namely Protestant Christianity and Catholic Christianity as minority religions. Adherents of different religions are very vulnerable to conflict. But for the residents of the Green Shapire Rasidance Housing, Ajibarang Wetan Village, the difference in religious background does not actually bring them into conflict. The purpose of this paper is to find out the forms of tolerance of local residents and the supporting factors of good tolerance in the housing. The research method used is a qualitative approach and the data used are descriptive data as well as a description of the daily lives of residents of housing communities, so that the most suitable approach is a qualitative approach. This study shows that the forms of tolerance that exist in the housing include two forms of tolerance. Namely religious tolerance and social tolerance. While the supporting factors for tolerance in the housing are because the residents adhere to the principle of harmony, the principle of respect and a high sense of solidarity